Perospirone augmentation of escitalopram in the treatment of an adolescent sophophobia (fear of learning) patient - Kensuke Miyazaki (Wiley, 2022)
Abstract In this case report, an adolescent boy with sophophobia (fear of learning) is reported. Although psychoeducation about the condition was helpful to the patient, there was only a limited effect on his symptoms. Psychotropic treatment with escitalopram was initiated. He showed gradual improvement with this treatment, and there was only a limited effect on his symptoms. Hence, the patient was referred for psychotherapy, although he was unable to attend sessions. Augmentation with perospirone resulted in significant improvement. Research about pharmacological approaches to treat childhood and adolescent phobias is limited and requires further investigation.